2021
DOI: 10.1016/j.jhin.2021.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare-associated infection impact with bioaerosol treatment and COVID-19 mitigation measures

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…ACTIVE Particle Control™ is effective on airborne particles of all sizes and very likely effective in clearing aerosolized bacteria and viruses. This work is consistent with other published studies ( 8 , 9 ).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…ACTIVE Particle Control™ is effective on airborne particles of all sizes and very likely effective in clearing aerosolized bacteria and viruses. This work is consistent with other published studies ( 8 , 9 ).…”
Section: Resultssupporting
confidence: 94%
“…ACTIVE Particle Control™ (APC) technology (SecureAire, Inc., Dunedin, FL) has been shown to reduce fine and ultrafine airborne particles and pathogens in live operating rooms, reduce bacterial contamination in active hospital compounding pharmacies, rapidly inactivate or kill the highly resistant Anthrax surrogate ( Bacillus subtilis ) in a research laboratory ( 8 ). APC has also reduced health care-associated infections by 45% ( 9 ). This novel technology works by local electromagnetic field manipulation (controlled ionization and polarization) ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…The novel coronavirus pandemic is the biggest public health crisis the world has faced in more than a century. Highly contagious and infectious SARS-CoV-2 causes bioaerosols that transport pathogenic microorganisms, thus affecting public health [ 12 ]. Clinical symptoms of COVID-19 are respiratory or cardiovascular complications [ 13 ].…”
Section: Background Information On Coronavirus Diseasementioning
confidence: 99%
“…As a crucial way to combat airborne pathogens, engineering control measures such as ventilation, air filtration, indoor pressure gradient control, and avoidance of recirculation have also played a key role in environmental safety [10] , [11] , [12] . A previous study found that the addition of engineering infection control measures without altering the traffic and workflow patterns of HCWs can reduce healthcare-associated infections by 45% [13] . Both traditional environmental infection control strategies and engineering controls are conducted during the operation stage of healthcare facilities.…”
Section: Introductionmentioning
confidence: 99%